2022
DOI: 10.1097/cm9.0000000000002208
|View full text |Cite
|
Sign up to set email alerts
|

Association between thyroid hormone levels and frailty in the community-dwelling oldest-old: a cross-sectional study

Abstract: Background: Changes in thyroid hormone levels are commonly recognized characters among the elderly, which were reported to potentially influence incident frailty. Therefore, we examined the cross-sectional associations of thyroid hormones (THs) with frailty as well as the five components characterizing frailty (fatigue, resistance, ambulation, number of illnesses, and loss of weight) among the oldest-old. Methods: Four hundred and eighty-seven community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
2
1
Order By: Relevance
“…While we hypothesized that hypothyroidism would show an association with frailty based on existing knowledge of thyroid dysfunction’s potential impact on various health parameters, neither overt hypothyroidism nor subclinical hypothyroidism was a significant factor in our results. In contrast to our findings, a recent study conducted in a population older than 85 years found that subclinical hypothyroidism and TSH levels were associated with frailty diagnosed using the FRAIL scale, which assesses Fatigue, Resistance, Ambulation, Illnesses, and Loss of weight [ 25 ]. Subclinical hypothyroidism has been associated with neuromuscular [ 26 ], musculoskeletal [ 27 ], and cognitive dysfunction [ 28 ], which all strongly correlate with frailty.…”
Section: Discussioncontrasting
confidence: 99%
“…While we hypothesized that hypothyroidism would show an association with frailty based on existing knowledge of thyroid dysfunction’s potential impact on various health parameters, neither overt hypothyroidism nor subclinical hypothyroidism was a significant factor in our results. In contrast to our findings, a recent study conducted in a population older than 85 years found that subclinical hypothyroidism and TSH levels were associated with frailty diagnosed using the FRAIL scale, which assesses Fatigue, Resistance, Ambulation, Illnesses, and Loss of weight [ 25 ]. Subclinical hypothyroidism has been associated with neuromuscular [ 26 ], musculoskeletal [ 27 ], and cognitive dysfunction [ 28 ], which all strongly correlate with frailty.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, several other studies have found a significant relationship between T3 levels and frailty, further supporting the notion that thyroid hormone levels, particularly T3, may be associated with the development and progression of frailty in the older population. 59,61,62 These findings highlight the potential importance of thyroid function in relation to frailty and call for further investigations to better understand the underlying mechanisms and clinical implications of these associations.…”
Section: Discussionmentioning
confidence: 96%
“…Triiodothyronine (T3), in particular, stimulates the myosin heavy chain of fast-twitch muscle fibers, leading to increased mitochondrial activity and an improved relaxation-contraction ratio. 58,59 These effects contribute to the overall functionality and performance of the musculoskeletal system. In our study, we observed a moderate negative correlation between T3 levels and the mean scores of fall risk and frailty, indicating that lower T3 levels were associated with higher levels of fall risk and frailty in the older adults (p<0.05).…”
Section: Discussionmentioning
confidence: 99%